Peningkatan Kreativitas dan Kepercayaan Diri Anak melalui Lomba Mewarnai Antar Taman Kanak-Kanak di Kecamatan Dempo Tengah Kota Pagar Alam - Eka Putra; Meriyanto Meriyanto (Jurnal Pengabdian Masyarakat, 2026)
The development of creativity and self-confidence in early childhood is an essential component in efforts to enhance children’s social welfare. Early childhood, often referred to as the “Golden Age,” represents a critical stage for brain development, creativity, as well as symbolic and imaginative thinking abilities. Creativity, as a key aspect of cognitive development, needs to be fostered from an early age because it plays a significant role in children’s problem-solving skills, imagination, and self-expression. The data collection techniques employed in this community service program included field observations and interviews. This activity was conducted at the Social Welfare Department Laboratory of the Institut Teknologi Pagar Alam, located at Jalan Masik Siagim No. 75, Simpang Bacang, Pagar Alam Utara District, Pagar Alam City, South Sumatra. The program was held on Tuesday, April 21, 2026, involving approximately 25 children, who were representatives from several kindergartens in Dempo Tengah District. Through this community service activity, participants were expected to improve children’s social welfare, creativity, and self-confidence. The results clearly demonstrated the uniqueness of each child’s creativity as well as their confidence in choosing colors, without hesitation in making their selections. This finding highlights the importance of fostering creativity and self-confidence in early childhood, particularly in enabling children to confidently express their choices and ideas through their artwork.